2023
DOI: 10.3390/app131810251
|View full text |Cite
|
Sign up to set email alerts
|

The Pulsed Electric Field Treatment Effect on Drying Kinetics and Chosen Quality Aspects of Freeze-Dried Black Soldier Fly (Hermetia illucens) and Yellow Mealworm (Tenebrio molitor) Larvae

Radosław Bogusz,
Katarzyna Pobiega,
Katarzyna Rybak
et al.

Abstract: Freeze drying is employed as one of the most effective preservation techniques, allowing dried material to be obtained characterized by high-quality properties. However, it also stands out as being one of the most energy-intensive methods and, consequently, expensive processes. Therefore, the objective of this study was to examine how the application of pulsed electric field (PEF) at 5 and 20 kJ/kg impacts the drying kinetics and the final quality of freeze-dried insects, including chemical composition, physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…The structural changes in the tissue due to the electroporation may have resulted in better solvent penetration into the material and improved the fat extraction yield [28,30], which was proved in a current study. A different effect of PEF application was reported by Alles et al [16], who studied convective-dried black soldier fly larvae and Bogusz et al [33] in previous study on freeze-dried black soldier fly and yellow mealworm larvae. These studies did not show any improvement in the oil extraction yield.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The structural changes in the tissue due to the electroporation may have resulted in better solvent penetration into the material and improved the fat extraction yield [28,30], which was proved in a current study. A different effect of PEF application was reported by Alles et al [16], who studied convective-dried black soldier fly larvae and Bogusz et al [33] in previous study on freeze-dried black soldier fly and yellow mealworm larvae. These studies did not show any improvement in the oil extraction yield.…”
Section: Discussionmentioning
confidence: 72%
“…The protein content was determined by the Kjeldahl method using a KjelFlex K-360 (Büchi, Flawil, Switzerland) nitrogen analyzer integrated with a TitroLine 5000 automatic titrator (SIAnalytics, Weilheim, Germany). The ash and moisture content were determined by the gravimetric method [33].…”
Section: Characterization Of Dried Black Soldier Fly Larvae 431 Chemi...mentioning
confidence: 99%
“…The protein content in insects after the PEF treatment was also elaborated upon in the related literature. For instance, the study performed on yellow mealworm larvae showed that the PEF application at 20 kJ/kg prior to freeze-drying significantly decreased protein content by 5.5% as compared to an untreated sample [16]. Psarianos et al [37] illustrated that the PEF-assisted extraction process of house cricket (Acheta domesticus) flour allowed the protein yield to increase, especially after PEF at 4.9 kJ/kg and an extraction time of 60 min.…”
Section: The Impact Of Pef Pretreatment and Drying Methods On Amino A...mentioning
confidence: 99%
“…In each experiment, about 350 ± 5 g of larvae were placed inside the treatment chamber, which was filled with tap water (σ = 220 µS/cm, t = 22 ± 1 • C) until the total mass of 1000 g was reached. The trials were carried out using an electric field strength of 1 kV/cm, and a specific energy intake (W spec ) at a level of 5, 20, and 40 kJ/kg was adjusted by applying electric pulses [16]. After treatment, the larvae were separated from the water, gently tapped with blotting paper, and then weighed.…”
Section: Pulsed Electric Field (Pef) Treatmentmentioning
confidence: 99%
See 1 more Smart Citation